Performing in extreme environments - Pedlar, C.; Whyte, G. (Strength and conditioning for sports performance, 2016)
Humans have evolved to live within narrow thermal limits and within a constricted altitude range, yet within these limits human physiology is remarkably adaptable. Technology has enabled humans to probe into environments that would not otherwise permit human survival: cruising in a pressurised cabin at 30,000 feet above sea level, with extreme outside temperature and pressure (around —40 °C and 226 mmHg); or scuba diving to 1,000 feet (300 m) below sea level, where the pressure is 31 atmospheres (the pressure at sea level is 1 atmosphere or 760 mmHg). Occupational scenarios exist in the emergency services, the forces, and maritime and aviation rescue services where workers are required to experienc e extreme conditions, for example desert warfare, search and rescue cold water immersion, and firefighting. Athletic competition in extreme environmental conditions is now becoming common, with an ever-growing list of extreme challenges to complement the established classics such as climbing Everest, the Marathon des Sables, swimming the English Channel, the Badwater Ultramarathon, Greenland`s Arctic Circle ski race and the Kona Ironman Triathlon. Olympic competition is rarely contested under extreme environmental conditions, depending on the definition of `extreme` applied. The highest summer Olympic Games were held in Mexico City in 1968 at around 2,200 m altitude, wakening the world of sport to the profound effects of altitude upon performance (positive and negative). Winter Olympic Games are regularly contested at moderate altitude where favourable snow conditions exist but extreme temperatures can prevail. In addition to variations in temperature and altitude other environmental factors affect performance, for example the pollution experienced at the 1984 Los Angeles Olympics. Pollution has the potential to exacerbate existing breathing problems such as asthma as well as reduce normal lung function and thus negatively affect performance. As a result, significant investment has been made by athletes and sports governing bodies in an attempt to prepare fully for the expected, and even unexpected, environmental conditions. The word `extreme` is perhaps overused and poorly applied; BMX, snowboard and other exciting, relatively young sports are given this label, and yet other more traditional sports may push the body beyond what would be considered normal and into a realm of extreme performance. Take the Boston Marathon in April 2012, where the temperature was 22 °C. This was not extreme, but 11 degrees above the average for the previous 27 years of the event. This difference resulted in 2,100 runners being treated for medical problems and over 260 hospitalisations (personal communications, Dr Aaron Baggish). During the later stages of the 50 km walk at the 2012 Olympic Games, a Russian athlete suffered a hyperthermic collapse despite the mild ambient conditions (18 °C, 50 per cent relative humidity). In this scenario, the heat source is predominantly metabolic in the absence of acclimatisation, causing hyperthermia to occur even in relatively cool conditions. Thus, it is difficult to define an extreme environment. Often, environmental stressors occur in combination, for example altitude and cold or heat/humidity and pollution. An integrated physiological response occurs, as a result of sensory information reaching the hypothalamus from multiple sources including the internal organs, skin and spinal cord. As a result, acute and chronic adjustments in blood flow, ventilation, cardiac output and sweat production are amongst the typical effects required for homeostasis and ultimately for survival. Any event can become an extreme challenge, owing, in part, to the environmental conditions. However, a major factor in success in sport in extreme environmental conditions is the physical condition and the specific preparation of the athlete. Acclimatisation (adaptation to the target environment) or acclimation (adaptation to a specific stressor) offers the athlete a major phenotypic advantage over an equivalent non-acclimatised competitor. A medical condition such as exercise-induced asthma may be exacerbated in an extreme environment and therefore needs to be prevented, or appropriately controlled, in advance of competition. Recovery from exercise training and performance may be affected by environmental conditions, for example a loss of sleep quality at altitude and in the heat. Furthermore, immune function is influenced bv environmental extremes. This chapter explores the specific challenges presented by hot, high, cold, deep and polluted environments. The emphasis is on the efficacy of appropriate techniques available to prepare and enhance performance in these environments.